Dynamic analysis with flat-top partition of unity-based discontinuous deformation analysis - Liu, Xiaoying (2019)
The flat-top partition of unity method can obtain a stiffness matrix with a small condition number and avoid the linear dependence problem. We aimed to extend the flat-top partition of unity method to rock dynamic analyses to simulate the influence of discontinuity and dynamic loading. Therefore, the flat-top partition of unity method was coupled with the discontinuous deformation analysis. In this paper, after the presentation of the mesh construction, the inertia force and contact algorithm for flat-top partition of unity-based discontinuous deformation analysis, several numerical examples are presented to verify the accuracy and efficiency of the method.